Low‐dose total‐body irradiation and alemtuzumab‐based reduced‐intensity conditioning regimen results in durable engraftment and correction of clinical disease among children with chronic granulomatous disease. (2nd April 2015) - Mehta, Bhakti; Mahadeo, Kris; Kapoor, Neena; Abdel‐Azim, Hisham
Abstract HSCT with MAC is associated with durable donor engraftment for patients with CGD; however, MAC is limited by high rates of RRT. We used a novel RIC regimen with LD‐TBI (200 cGy × two doses), fludarabine (30 mg/m2 × three doses), and proximal alemtuzumab (0.5 mg/kg/dose × one dose) and unrelated donor grafts for consecutive patients with high‐risk CGD who were not candidates for MAC at our institution. Among four children with CGD transplanted at our institution, three PBSC recipients are alive with sustained donor engraftment (median follow‐up: two yr) and resolution of pre‐HSCT active infections while one patient with bone marrow graft is alive after graft failure and autologous recovery. RIC may be a curative option for children with high‐risk CGD.